Структурно-термоатмогідролого-геохімічні дослідження Бобриківської западини - Багрій, І.Д.; Гордєєва, Ю.К.; Глонь, В.А.; Куліш, А.П.; Стародубець, К.М. (Геоінформатика, 2017)
Проаналізовано результати комплексних структурно-термоатмогідролого-геохімічних досліджень (СТАГГД), проведених на території Бобриківської западини (північ Дніпровсько-Донецької западини). Проблема пошуків і розвідки перспективних ділянок на видобуток вуглеводнів особливо актуальна з переходом нафтогазової промисловості України на освоєння невеликих за розмірами родовищ. З використанням нового комплексу СТАГГД уперше всебічно досліджено та закартовано перспективні на пошуки вуглеводнів ділянки Бобриківської западини. Зіставлено геолого-геофізичні матеріали з результатами аерокосмічного дешифрування території, отримано карти розподілу температурного показника, радону, торону, гелію, водню, вуглекислого газу, метану та його гомологів. Виділено ділянки, перспективні на пошуки вуглеводневої сировини. Проанализированы результаты комплексных структурно-термоатмогидролого-геохимических исследований (СТАГГИ), проведенных на территории Бобриковской впадины (север Днепровско-Донецкой впадины). Проблема поисков и разведки перспективных участков на добычу углеводородов особенно актуальна с переходом нефтегазовой промышленности Украины на освоение небольших по размерам месторождений. С использованием нового комплекса СТАГГИ впервые всесторонне исследованы и закартированы перспективные на поиски углеводородов участки Бобриковской впадины. Проведено сопоставление геолого-геофизических материалов с результатами аэрокосмического дешифрирования территории, получены карты распределения температурного показателя, радона, торона, гелия, водорода, углекислого газа, метана и его гомологов. Установлено, что полученные атмогеохимические показатели соответствуют геологическому строению района исследований. Выделены участки, перспективные на поиски углеводородного сырья. Purpose. The aim of the study was to carry out a comprehensive study and mapping of promising sites in search of hydrocarbons on the territory of the Bobrikivska depression by applying STAHGR technology. The main objectives of the work were the following: to construct conceptually new graphs based on the data obtained, to compare them with the available geological and geophysical data, and to identify promising areas for further searching for hydrocarbons.
Design/methodology/approach. The study is based on a comprehensive technology of structural and thermo-atmo- hydrological and geochemical research (STAHGR), which consists of the following structural and functional units: thermo-atmo-geochemical field studies including geothermic, radiometric studies and a soil vapor survey (for free hydrocarbons - methane, ethane, propane, butane, isobutane, ethylene, propylene, and also radon, thoron, helium, hydrogen, carbon dioxide). The purpose of this survey is to identify anomalies of hydrocarbons migrating from deposits of oil, gas and gas condensate. The main target of applying geochemical techniques on the land is the subsoil at the depth of 100-120 cm. The mapping feature is a spatial combination of background values of atmo-geochemical indicators and positive temperature anomalies delineated by gas and emanation maxima.
Findings. This was the first attempt ever to carry out a comprehensive study and mapping of promising sites in search of hydrocarbons within the Bobrikivska depression. We have conducted a comparison of available geological and geophysical data with the results of satellite image interpretation; we have constructed radon, thoron, helium, hydrogen, carbon dioxide, methane, and its homologues and temperature distribution maps. We have made a comparison of the obtained atmo-geochemical parameters with the geological structure of the studied area, which results in a better understanding of the geological structure and geodynamic processes of the territory under investigation.
Practical value/implications. We have defined the prospects of searching for hydrocarbon deposits within the edges and near edge zones of the Bobrikivska depression. It is estimated that there are a non-anticlinal hydrocarbon traps within the northern edge. The results of the investigation confirm the high potential of the Bobrikivska depression and can be used as reference in studying other depressions of the Dnieper-Donets Basin.